1104 Introducing a new paediatric clerking proforma in a tertiary paediatric emergency department – a quality improvement project. (17th August 2022) - Stankovikj, Vera; Davis, Ailish; Jenner, Rachel
Abstract : Aims: Tailored admission documents for clerking of acutely unwell paediatric patients have been shown to improve the thoroughness of medical documentation in paediatric assessment units. However, this has not previously been demonstrated in a tertiary paediatric emergency department (PED) where the high patient turn-over, requirement for prompt clinical decision-making and variable paediatric experience of emergency medicine clinicians are some of the challenges the department faces on a regular basis. The aim of this quality improvement project was to generate, assess and implement a new paediatric clerking proforma to be used by emergency medicine clinicians in the PED at our institution. Methods: To evaluate the quality of the paediatric clerking documentation at baseline, we assessed 35 randomly selected PED clinical records against 21 parameters set as standards of paediatric history. The findings were then used as a baseline to develop a new PED clinical record. The initial draft of the new PED clinical record was trialled on three separate occasions: 29, 19 and 15 PED clinical records were assessed as part of the 1st, 2nd and 3rd trials respectively. In addition, qualitative feedback from both the medical and nursing staff was collected at the end of each trial, which was then used to further improve the new PED clinical record. On completion of the final trial, the original clerking proforma was replaced with the final version of the newly generated PED clinical record. This remains subject to continuous evaluation. Results: Prior to introducing the new PED clinical record, we identified multiple gaps in the paediatric history with regards to: past medical history, development, allergies, immunisations and medications. Inconsistencies in the paediatric clerking documentation were dependent on the grade and experience of the PED clinician. There was an increase in the number of paediatric history parameters recorded by clinicians when using the new PED clinical record compared with the original PED record. Data input was significantly greater in the new PED clinical record for sections relating to: development ( 40% increase, p<0.001), medications ( 30% increase, p<0.05), allergies ( 25% increase, p<0.05) and immunisations ( 30% increase, p<0.05). This is summarised in figure 1. At the end of the trialling period, after a thorough review of the qualitative feedback received, the final version of the new PED clinical record was implemented in the PED at our institution. Conclusion: Consistent and age-specific history taking is an important part of the clinical assessment in emergency paediatrics as poor clinical information gathering may lead to errors in both diagnosis and management. Here we have demonstrated that a purpose-designed paediatric clerking proforma improves the quality and consistency of medical documentation, irrespective of the PED clinician's grade and paediatric experience. This successful development of a dedicated PED clinical record, has allowed further quality improvements such as a single clerking process between the PED team and the paediatric teams to be introduced. Lastly, the new proforma will be used as a baseline when PED at our institution transitions to electronic clerking.